Training needs assessment of the katilingban sng mga pumoluyo nga naga atipan sang watershed (kapawa), Maasin, Province of Iloilo - Pajanustan, Dalmacio L. (University of the Philippines in the Visayas, 2005)
This study was conducted to assess the training needs of the officers and members of the Katilingban sng mga Pumoluyo nga naga-Atipan sng Watershed (KAPAWA), a Federation of people's organization within the Maasin watershed, Province of Iloilo. The 48 respondents were randomly chosen from the list officers and members of KAPAWA residing in the seven barangays in the municipality of Maasin, Iloilo. Data were gatherd using an interview schedule and data were analyzed using descriptive statistics. The study revealed that officer-respondents need knowledge competencies on sustainable development concepts, livelihood project development, orientation to environmental laws, and resource management. They consider trainings on policy formulation, review, and implementation, project monitoring and evaluation, organizational management and development, project development, project management and conflict management as "somewhat needed" for their organizational capability building and empowerment while knowledge on human resource management, situational analysis, record management, strategic planning, marketing concepts, principles and methods, and training management are not their priorities.